The comparative effects of oral famotidine and lansoprazole in prophylaxis of aspirin induced peptic ulcer in albino rat - Bhushan, Rabi; Kumar, Ratan; Chandra, Akash; Singh, Haribansh Kumar (International Journal of Research in Medical Sciences, 2021)
Background: Peptic ulcer is defined as any break in the continuity of gastric or duodenal epithelial layer. There are mainly three factors which are responsible for peptic ulcer disease which are Helicobacter pylori infections, NSAIDs and stress. Famotidine is H2 receptor blocker and Lansoprazole is proton pump inhibitor which are used prophylactically in aspirin induced peptic ulcer. Methods: The experimental work was carried out on albino rat. Experiment was carried out with two ulcer protecting agents e.g-famotidine, lansoprazole and one ulcer producing agent Aspirin. Each ulcer protecting drug was used separately but simultaneously with aspirin to see their ulcer protecting efficacy. There was three groups of animals each consisting of ten albino rats. Ist group was control group which was given aspirin only.2nd group was given aspirin+famotidine, 3rd group was given aspirin+lansoprazole. Results: The prophylactically ulcer preventing activity was the most with lansoprazole and least with famotidine. Conclusions: Finally, all the two drugs like famotidine, lansoprazole prevented the ulcerogenic effects of Aspirin effectively, although not completely.